2017
DOI: 10.1002/adma.201700256
|View full text |Cite
|
Sign up to set email alerts
|

Selective Coloration of Melanin Nanospheres through Resonant Mie Scattering

Abstract: Black melanin inks are prepared to selectively exhibit colors under strong light, inspired by human hair. High absorbance of melanin suppresses multiple scattering, causing resonant Mie scattering predominant. Various colors can be developed as the resonant wavelength dictated by nanosphere diameter. Therefore, the melanin inks can be used to encrypt and selectively disclose multicolor patterns for anticounterfeiting applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…These disordered elements in the ordered HNFs result in removal of the directionality, which is essential for a noniridescent color reflector, as found in a morpho butterfly 19 . This phenomenon is comparable to the case of the close-packed structure-based color reflectors such as photonic crystals comprising colloidal particles 20,21 .…”
Section: Optical Properties Of the Fabricated Structural Color Reflecsupporting
confidence: 54%
“…These disordered elements in the ordered HNFs result in removal of the directionality, which is essential for a noniridescent color reflector, as found in a morpho butterfly 19 . This phenomenon is comparable to the case of the close-packed structure-based color reflectors such as photonic crystals comprising colloidal particles 20,21 .…”
Section: Optical Properties Of the Fabricated Structural Color Reflecsupporting
confidence: 54%
“…As the concentration decreases from 1 to 0.01 wt% for the 307‐nm nanospheres in ethanol, we see that the suspensions become more translucent, but the color remains, albeit weaker in intensity ( Figure e). We expect no structural correlations at such low concentrations, though we do expect the reflectance peaks to red‐shift owing to the different refractive index of the medium . Indeed, single‐scattering calculations of the nanospheres in ethanol again agree with the measured reflectance peaks (Figure c).…”
supporting
confidence: 54%
“…An alternative approach is to rely on the wavelength‐dependent scattering of the particles themselves. Cho et al demonstrated that colloidal particles of light‐absorbing melanin show colors due to Mie resonances. The melanin or polydopamine in the particles suppresses multiple scattering owing to its strong absorption, but the colors are visible only under intense directional illumination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that melanin in human hair exists in the form of melanin granules, which was reported to contain plenty of functional groups such as amino, carboxyl, and indolyl groups (Cho et al, 2017;Mostert et al, 2018;D'Ischia et al, 2014). In our previous study, natural melanin particles (NMPs) were extracted from human hair by using alkaline-degradation method, also confirming the presence of functional groups (Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 62%